Human Resource Development for Health in Indonesia: Challenges of Achieving the Millennium Development Goals - Kurniati, Anna; Efendi, Ferry; Yeh, Pi-Ming (Pusat Perencaan dan Pendayagunaan SDM Kesehatan, BPPSDMK, 2014)
The development of Human Resources for Health (HRH) is one of the keys to achieving The Millennium Development Goals (MDG). Providing and ensuring the best health care service in every region of Indonesia has long been a major concern. Several challenges faced by HRH development are a shortage of professionals, uneven distribution of professionals between regions, a variety of settings (urban and rural), and management of the health workforce under a decentralization system.